Effects of late-summer protein supplementation on stocker cattle performance, feedlot gain, and carcass traits - Marston, T.T.; Yauk, D.O.; Wankel, L.E.; Gleghorn, J.F. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A 2-year trial was conducted to study the effects of feeding an Arsoy™-based, 32% crude protein supplement to stocker cattle grazing late-summer native pastures. During about 90 days of late-summer/fall grazing, the steers efficiently converted the Arsoy supplement (5.3:1, as fed basis) into significantly greater weight gains (55 lb) relative to nonsupplemented contemporaries. Both groups of steers then were finished and slaughtered in commercial facilities to determine if the supplementation program had any carryover effects. Late-summer supplementation did not influence steers’ feedlot gain or carcass traits including ribeye area, fat thickness, and quality grade. However, average hot carcass weight and yield grade of pasture-supplemented steers were significantly greater than those of controls. Our study demonstrates that Arsoy makes an excellent protein supplement for growing cattle on maturing native grass pastures. In addition, the added stocker gains did not influence feedlot performance and had minimal effects on carcass traits.
Keywords: Beef; Stocker cattle; Protein; Supplementation